2018
DOI: 10.1590/1413-812320182312.34972016
|View full text |Cite
|
Sign up to set email alerts
|

Políticas de Saúde e de Segurança Alimentar e Nutricional: desafios para o controle da obesidade infantil

Abstract: Resumo O estudo analisou as ações de prevenção e controle da obesidade infantil, especialmente as de Promoção da Alimentação Adequada e Saudável (PAAS), que integram Políticas do governo federal brasileiro nos últimos 15 anos. Foram analisados todos os documentos que apresentam ações de PAAS no âmbito das políticas de saúde e segurança alimentar e nutricional a partir das seguintes dimensões: (1) a abordagem das ações de PAAS; (2) os condicionantes da obesidade que pretendem afetar e (3) as potenciais disputas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
43

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 19 publications
1
16
0
43
Order By: Relevance
“…In Brazil, one of the commitments of the Political Nacional de Alimentação e Nutrição (PNAN, National Food and Nutrition Policy) is the continuous and systematic monitoring of the population's food and nutritional situation [3]. Periodic food consumption data allows researchers to know the main changes and temporal trends, to identify eating behaviors which could be harmful to the health of the population, to monitor the effectiveness of interventions and to subsidize public policies [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, one of the commitments of the Political Nacional de Alimentação e Nutrição (PNAN, National Food and Nutrition Policy) is the continuous and systematic monitoring of the population's food and nutritional situation [3]. Periodic food consumption data allows researchers to know the main changes and temporal trends, to identify eating behaviors which could be harmful to the health of the population, to monitor the effectiveness of interventions and to subsidize public policies [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of our study is related to the cross-sectional design that, although useful for the diagnosis of child health, does not allow us to evaluate the temporal sequence between exposure and outcome of interest. Cross-sectional studies may present difficulty in interpreting the outcome studied and the variables analyzed since there is the possibility of reverse chance bias, which occurs when apparent exposure is a consequence of the outcome, as reported by other studies [39][40][41][42][43] . Based on the results presented, it is suggested that measures to control and prevent health risks associated with childhood obesity are necessary, taking as an incentive action for a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…As compras públicas permitem a oferta de alimentos frescos, variados e nutritivos, melhorando a qualidade da alimentação para a população. Além disso, possibilitam a abertura de novos mercados para a agricultura familiar, estabelecimento de marcos legais mais justos aos agricultores, participação social, desenvolvimento local, articulação de políticas públicas e valorização da agricultura familiar na sociedade (19).…”
Section: Eixo 1: Disponibilidade E Acesso a Alimentos Adequados E Sauunclassified
“…As ações regulatórias buscam definir limites entre sociedade e Estado e entre governo e mercado na garantia dos direitos constitucionais e do bem público. Assim, criam diretrizes para a atuação dos setores comerciais e objetivam proteger a população contra práticas abusivas, especialmente oriundas do setor privado comercial (19). Agências internacionais, governos, consumidores, empresas e instituições científicas desempenham papéis estratégicos e participam da definição de alternativas por meio de diferentes mecanismos e arenas.…”
Section: Eixo 6: Regulação E Controle Da Qualidade E Inocuidade De Alunclassified
See 1 more Smart Citation